1986
DOI: 10.1044/jshd.5101.53
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mild and Moderate Hearing Impairments on Language, Educational, and Psychosocial Behavior of Children

Abstract: An extensive psychoeducational evaluation was administered to 40 hearing-impaired children to investigate the effects of degree of hearing impairment, age, and other factors on intellectual, social, academic, and language behavior. Although children varied greatly in performance, hearing loss of any degree appeared to affect psychoeducational development adversely, leading to the conclusion that even minimal hearing loss places children at risk for language and learning problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
261
2
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(283 citation statements)
references
References 9 publications
11
261
2
9
Order By: Relevance
“…In the current work, the four-frequency PTA inclusion criterion incorporates characteristics of the children's high-frequency hearing, which is likely to result in a slightly higher PTA value than would be found using a three-frequency PTA due to sloping configurations of HL (Pittman & Stelmachowicz, 2003). This broader definition is also consistent with previous research including children with mild HL (Blair, Peterson, & Viehwig, 1985;Davis, Elfenbein, Schum, & Bentler, 1986;Fitzpatrick, Durieux-Smith, & Whittingham, 2010;Fitzpatrick et al, 2016;Fitzpatrick, Whittingham, & DurieuxSmith, 2014;Sininger, Grimes, & Christensen, 2010).…”
supporting
confidence: 75%
See 1 more Smart Citation
“…In the current work, the four-frequency PTA inclusion criterion incorporates characteristics of the children's high-frequency hearing, which is likely to result in a slightly higher PTA value than would be found using a three-frequency PTA due to sloping configurations of HL (Pittman & Stelmachowicz, 2003). This broader definition is also consistent with previous research including children with mild HL (Blair, Peterson, & Viehwig, 1985;Davis, Elfenbein, Schum, & Bentler, 1986;Fitzpatrick, Durieux-Smith, & Whittingham, 2010;Fitzpatrick et al, 2016;Fitzpatrick, Whittingham, & DurieuxSmith, 2014;Sininger, Grimes, & Christensen, 2010).…”
supporting
confidence: 75%
“…It should be noted, however, that there are limitations in interpreting these prior studies with regard to the importance of early identification and intervention for children with mild HL. Much of the available research was conducted with populations of children who did not have access to NHS, and thus the children were identified later, on average, than might be expected for children with mild HL born in the post-NHS era (Blair et al, 1985;Davis et al, 1986;Đoković et al, 2014;Wake et al, 2006;Wolgemuth et al, 1998).…”
Section: Developmental Outcomes and Service Provision In Children Witmentioning
confidence: 99%
“…[12][13][14][15][16][17] Findings of suboptimal academic skills have been reported in school age children with mild bilateral HL. [27][28][29][30][31][32][33][34][35] Other investigators have reported delayed development of vocabulary and speech skills in children with unilateral HL. 36,37 Although it has been reported that children with unilateral rightsided HL have poorer performance on verbal tests than children with left ear unilateral HL, 16 our cohort was too small and diverse to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Using this technique, the carotid artery need not be sacrificed and the normal pulsatility to the systemic flow is maintained. The risk for central nervous system complications (bleeding, microthrombi or infarct) seems to be less in VV-ECMO than in VA-ECMO (33 (35,36). It seems, therefore, to be important to detect HL at an early stage and provide early intervention.…”
Section: Discussionmentioning
confidence: 99%